2022
DOI: 10.3390/ijerph19042059
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Cannabis Use Trajectories and Outcomes in a Sample of Hispanic, White, and Asian Sexual and Gender Minority Emerging Adults

Abstract: Substance use disproportionately affects health and psychosocial outcomes for some racial/ethnic groups, but few longitudinal studies examine the extent to which sexual and gender minority (SGM) emerging adults of different racial/ethnic groups may experience disparities in outcomes at similar levels of alcohol or cannabis use. This study used five waves of annual survey data (spanning 2015 (average age 18) to 2020 (average age 23)) from an ongoing longitudinal cohort study of emerging adults. In the subset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…There is much less work assessing disparities in outcomes due to AOD use among SGM individuals. To date, our team has addressed this by examining how trajectories of alcohol and cannabis use from adolescence through emerging adulthood are prospectively associated with differences in a range of health and psychosocial outcomes for SGM compared to non-SGM emerging adults (Dunbar et al, 2022a(Dunbar et al, , 2022b. This work indicates that SGM individuals show steeper increases in cannabis use, but not alcohol use, throughout adolescence and into emerging adulthood.…”
Section: How the Strata Cohort Study Is Addressing Aod Use Disparitiesmentioning
confidence: 99%
“…There is much less work assessing disparities in outcomes due to AOD use among SGM individuals. To date, our team has addressed this by examining how trajectories of alcohol and cannabis use from adolescence through emerging adulthood are prospectively associated with differences in a range of health and psychosocial outcomes for SGM compared to non-SGM emerging adults (Dunbar et al, 2022a(Dunbar et al, , 2022b. This work indicates that SGM individuals show steeper increases in cannabis use, but not alcohol use, throughout adolescence and into emerging adulthood.…”
Section: How the Strata Cohort Study Is Addressing Aod Use Disparitiesmentioning
confidence: 99%
“…Several studies have found that sexual minority youth are more likely to start drinking at younger ages ( Phillips et al, 2019 , Schuler and Collins, 2019 , Talley et al, 2019 ) and this may help explain elevated rates of negative alcohol outcomes (e.g., AUDs) given that early age of drinking onset is associated with the development of AUDs ( Cheng et al, 2016 , Lopez-Quintero et al, 2011 ). Supporting this contention, several ( Coulter et al, 2018 , Marshal et al, 2009 , Marshal et al, 2012 ), but not all ( Dunbar et al, 2022a , Dunbar et al, 2022b , Talley et al, 2012 ), cohort studies have identified sharper increases in alcohol use trajectories among sexual minorities in early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our sample included a large percentage of sexual gender minority (SGM) individuals. Previous studies have shown that SGM individuals report greater consequences at the same levels of alcohol and cannabis use compared to their non-SGM peers (Dunbar et al, 2022a;Dunbar et al, 2022b). Furthermore, research with lesbian, gay, bisexual, and two-spirit Native American people has shown that these individuals tend to report higher rates of AOD use (Balsam et al, 2004) and also experience more health disparities compared to their non-SGM peers (Wilson et al, 2021).…”
mentioning
confidence: 99%